2010
DOI: 10.1111/j.1600-0706.2009.17956.x
|View full text |Cite
|
Sign up to set email alerts
|

Compensating for delayed hatching across consecutive life-history stages in an amphibian

Abstract: Environmental conditions experienced early in the ontogeny can have a strong impact on individual fi tness and performance later in life. Organisms may counteract the negative eff ects of poor developmental conditions by developing compensatory responses in growth and development. However, previous studies on compensatory responses have largely ignored the eff ects that poor embryonic conditions could have during the later life stages. In this study, we examined the eff ects of artifi cially delayed developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 65 publications
(96 reference statements)
12
43
1
Order By: Relevance
“…In accordance with previous studies (Orizaola et al 2010), we also found that growth and development rates increased in response to the delayed hatching treatment. This response could have been brought about by the time-keeping mechanisms of the embryos, as mentioned above, or be a direct response to low temperature during embryonic development, as found during later developmental stages (Dahl et al 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with previous studies (Orizaola et al 2010), we also found that growth and development rates increased in response to the delayed hatching treatment. This response could have been brought about by the time-keeping mechanisms of the embryos, as mentioned above, or be a direct response to low temperature during embryonic development, as found during later developmental stages (Dahl et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Twelve hours after fertilization, each clutch was divided into four 5 L plastic vials with reconstituted soft water (see Orizaola et al [2010] for details). Two vials from each family were maintained in a climatecontrolled room at constant 168C, whereas the other two were transferred to a 48C and 16 h light : 8 h dark photoperiod climate-controlled room for six days, after which they were transferred back to the 168C and 16 h light : 8 h dark room.…”
Section: Experimental Design and Laboratory Conditionsmentioning
confidence: 99%
“…Shorter development time in years with late breeding is adaptive and agrees with previous studies reporting accelerated life history in latehatching animals (Carrière et al 1996;Johansson et al 2001;Altwegg 2002;De Block and Stoks 2004;Stoks et al 2006;Orizaola et al 2010), though the costs of higher growth and development rates could compromise individual fitness later in life (Dmitriew 2011). Early egg-laying in northern localities allowed tadpoles to extend their larval period by more than 15 % and metamorphose at on average 25 % higher mass than late-hatching individuals from the same localities.…”
Section: Discussionsupporting
confidence: 84%
“…Although larvae generally react to these changes (Johansson et al 2001;De Block and Stoks 2004;Stoks et al 2006), the responses were in some cases independent of photoperiod, suggesting that they may have a genetic basis or be maternally determined (De Block and Stoks 2004). In our case, larval responses were not induced by photoperiod, since under the laboratory conditions photoperiod was kept similar and constant for all the populations and treatments throughout the study (see Orizaola et al 2010 for similar results). On the other hand, in birds female hormone levels respond to modifications of environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 55%
“…several recent reviews document hatching plasticity in species throughout the Bilateria, in response to cues that range from physical disturbance to natural enemies and resource limitation (Doody 2011;Warkentin 2011aWarkentin , 2011b. thus, induced changes in life history switch points are common, and the phenotypic differences arising from them may have important consequences for shaping species interactions and performance in subsequent stages (altwegg and reyer 2003;Vonesh and Bolker 2005;Orizaola et al 2010;Dahl et al 2012;touchon et al 2013).…”
Section: Introductionmentioning
confidence: 99%